UPAYA GURU DAN ORANG TUA DALAM MENGATASI SISWA KESULITAN BELAJAR DI SDN JAMBU BURUNG KABUPATEN BANJAR - Siti Faridah; Maria Ulfah (Pahlawan Jurnal Pendidikan-Sosial-Budaya, 2021)
The purpose of this study was to determine the causal factors and the efforts of teachers and parents in overcoming students who have learning difficulties in thematic learning. This type of research uses a qualitative approach using descriptive methods. The subjects of this study were homeroom teachers for fourth grade, fourth grade students who had learning difficulties, and parents of students who had learning difficulties. Data collection techniques used interviews, observation, and documentation. Data analysis used the Milles n Hubberman model with qualitative descriptive analysis methods, namely data reduction, data presentation, and drawing conclusions. Data processing used data triangulation. The results showed that the factors causing students to experience thematic learning difficulties were the lack of student motivation, lack of tutoring at home, ineffective teacher teaching techniques and lack of environmental supervision of students. Efforts made by teachers and parents in overcoming students who have learning difficulties in thematic learning, are by conducting consultations between teachers and parents of students, where schools can prepare and facilitate, movements for solving social problems in schools, teachers use teaching methods which varies, teachers and parents provide learning motivation to students, parents are committed to guiding students to study at home, giving more attention to children. It is hoped that this research can be used as a lesson about the efforts of teachers and parents in overcoming thematic learning difficulties.